Etnisitas sebagai Instrumen Politik dan Keamanan di Kalimantan Barat Pasca Rezim Orde Baru - - Jumadi; Mohammad Rizal Yakoop (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
Political changes of the New Order regime have an impact on the dynamics of local politics in West Kalimantan. These changes raise complex issues related to ethnic and religious issues in the rivalry between Dayak and Malay elite. Therefore, this article aims to study the ethnic as an instrument of politics post New Order regime 1999-2008 case West Kalimantan and link into political representation and the community security by utilizing qualitative approach. In addition, the data for this study is based on primary and secondary data. The primary data obtained through in-depth interviews with selected informants. While the secondary data obtained from books and journals. This writing used the conceptual framework of Jack Snyder (2000) about democratizing states and ethnic nationalism and Ted Robert Gurr (1994) on ethno politic and instrumentalism approach. The study found some important factors that influence the emergence of identity politics in West Kalimantan, namely structural factors, political conditions, unbalanced representation of political and ethnic stereotypes. However, political factors and unbalanced ethnic representation in power are the main causes of the emergence of identity politics in West Kalimantan. The results also show that the occurrence of ethnic identity politics and religion has influence on the shape of political representation and community security.